Microwave-Pyrolysed Rice Husk-Derived Activated Carbon as a Sustainable Anode Material for Lithium-Ion Half-Cell Batteries - Surib , Nur Atiqah; Mohd Abdah, Muhammad Amirul Aizat; Farhana Syakirah Ismail; Wong, Weng Pin; Ab Latif, Farah Ezzah; Mustafa, Muhammad Norhaffis; Rashmi Walvekar; Mohammad Khalid (Science and Technology Research Centre Universitas PGRI Semarang, 2026)
Agricultural waste biomass is explored as a sustainable precursor for activated carbon. In this study, rice husk-derived activated carbon (RHAC) was synthesized via microwave-assisted pyrolysis and KOH activation at 600, 700, and 800 °C. The KOH activation enhanced the thermal stability of the samples, with RHAC_700 exhibiting a spongy, interconnected structure and a surface area of 390.33 m² g⁻¹. When evaluated as a half-cell anode materials for lithium-ion batteries, RHAC_700 delivered an initial discharge capacity of approximately 388.33 ± 11.65 mAh g⁻¹ with Coulombic efficiency 68.29 % and stabilized at 250.00 ± 7.33 mAh g⁻¹ with 99.82% of Coulombic efficiency after 100 cycles at 0.2 A g⁻¹ and 25 °C (active material loading: 0.95 ± 0.15 mg cm⁻²). All reported values represent the average of three independent cells. Furthermore, RHAC_700 demonstrated good rate capability, retaining capacities from 248.33 ± 7.45 mAh g⁻¹ to 134.58 ± 4.04 mAh g⁻¹ at current densities ranging from 0.2 to 1.0 A g-1.